2014
DOI: 10.1063/1.4893898
|View full text |Cite
|
Sign up to set email alerts
|

Band filling effects on temperature performance of intermediate band quantum wire solar cells

Abstract: Articles you may be interested inInGaAs/GaAsP strain balanced multi-quantum wires grown on misoriented GaAs substrates for high efficiency solar cells Appl. Phys. Lett. 105, 083124 (2014); 10.1063/1.4894424 Theoretical analysis of GaAs/AlGaAs quantum dots in quantum wire array for intermediate band solar cell Detailed studies of solar cell efficiency as a function of temperature were performed for quantum wire intermediate band solar cells grown on the (311)A plane. A remotely doped one-dimensional intermediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
(32 reference statements)
2
6
0
Order By: Relevance
“…In addition, the C-V measurements at T=20 K revealed plateaux in QWR undoped devices which were related to 2DEG or/and the carrier accumulation in the QD layer, and for the QWR doped devices the i th steps observed in the C-V plots were related to the depletion of the i th QWR in the devices. The efficiency and EQE characteristics obtained by Kunets et al [15] at different temperatures correlated with the appearance of trap peaks observed in the DLTS and…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…In addition, the C-V measurements at T=20 K revealed plateaux in QWR undoped devices which were related to 2DEG or/and the carrier accumulation in the QD layer, and for the QWR doped devices the i th steps observed in the C-V plots were related to the depletion of the i th QWR in the devices. The efficiency and EQE characteristics obtained by Kunets et al [15] at different temperatures correlated with the appearance of trap peaks observed in the DLTS and…”
Section: Resultsmentioning
confidence: 98%
“…The integrated GaAs EQE measurements showed an obvious U-shape trend as a function of temperature for QWR undoped devices, however, for the reference PIN devices the GaAs EQE characteristics were almost temperature independent. In this study [15], this behaviour can be associated to the electrically active traps E2 QWR and E3 QWR since they were detected within the temperature ranges where the solar conversion efficiencies were low. Although the PIN and QWR undoped devices have similar defects in terms of activation energy, the capture cross-sections of the QWR undoped devices are higher.…”
Section: Dlts and Laplace Dlts Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations